Genotoxic evaluation of infusions of Urera baccifera leaves and roots in Allium cepa cells - Amanda L. Gindri; Ana Paula D. Coelho; Solange B. Tedesco; Margareth L. Athayde (GarVal Editorial Ltda., 2015)
Context: The aqueous extracts of Urera baccifera Wedd. leaves and roots are used to inflammatory and infectious diseases in Brazilian folk medicine. Oxalic acid, a substance co-related with toxicity and stinging, was already quantified in this plant. Aims: To evaluate the action of leaves and roots infusions (1, 30, 75 g/L) and the oxalic acid standard on mitosis as indicative of presumably antimitotic and genotoxic actions, using the Allium cepa test. Methods: Oxalic acid was quantified in the roots and leaves infusions by High-performance liquid chromatography (HPLC-DAD), with the mobile phase of 25 mM phosphate buffer (pH 2.5): acetonitrile at 95:5 (v/v). To the genotoxicity test, onion bulbs were used. After the rootlets germination, each bulb was submitted for 24 h of the individual treatments. Were analyzed 1000 cells per bulb, in a total of 5000 cells per treatment. Results: Results showed that all concentrations of roots infusions induced chromosomes abnormalities, except for the highest, that caused a substantial inhibition in the mitosis, precluding to be observed abnormalities. In the leaves infusions, only the two higher concentrations caused the highest values of damage in the cellular cycle. The oxalic acid also caused abnormalities in the mitosis, and may be considered responsible by part of the genotoxic action of U. baccifera. Conclusions: Oxalic acid can be responsible by part of the chromosomal abnormalities caused by U. baccifera, although, there must have more metabolites that evoke the same effect promoting the genotoxic effect of this nettle.